IMPLEMENTING DIGITALIZATION TO PROMOTE CIBULUH CULTURAL TOURISM VILLAGE - Firman Syah; Imam Syafganti (ZILLZELL MEDIA PRIMA, 2025)
Village tourism destinations are currently a crucial pillar in community-based economic development. Furthermore, Indonesia boasts extraordinary cultural and natural diversity. Cibuluh Tourism Village, located in Subang Regency, West Java, is a destination that maintains its cultural potential by combining nature and local wisdom as its main attractions. Digitalization here is not only about the application of technology, but also about restructuring governance, community participation, and village image. The purpose of this study is to implement technology for promotional activities in Cibuluh Tourism Village and explain the promotions implemented in Cibuluh Tourism Village. The research type chosen is quantitative with numerical data analysis to explain, predict, and control the phenomena of interest, processed using statistical methods. The results of the research from the implementation of technology for promotional activities that can be implemented in Cibuluh Tourism Village in order to attract tourists while maintaining local wisdom are utilizing the availability of supporting facilities and infrastructure that are highly dependent on the readiness of the local community (Pokdarwis) and the role of the local government, as well as budgetary assistance. Meanwhile, promotional activities in Cibuluh Tourism Village include several hardware and software-based promotional tools, including laptops, mobile phones, drones, and GPS. There's also a website, Facebook, Instagram, TikTok, and YouTube.